Pedagogical and Social Factors Influencing the Development of Students’ Legal Culture (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article explores the pedagogical and social factors influencing the formation and development of students’ legal culture in the context of building a law-governed state and a civil society. It highlights that legal culture is a complex social phenomenon that encompasses legal knowledge, legal awareness, and legal activity, which together determine an individual’s attitude toward law and justice. The author emphasizes the decisive role of family, educational institutions, state organizations, and the media in shaping the legal consciousness of young people. The paper also examines ongoing reforms and educational initiatives in Uzbekistan, such as the “Youth – Our Future” program, “Street Law,” “Advocacy Train,” and “Legal Clinic” projects, aimed at increasing legal literacy and awareness among the population. The study concludes that the enhancement of youth legal culture is a key prerequisite for the establishment of a democratic, law-based, and just society.